A study on sales analysis (electricity) by Sabah Electricity Sdn Bhd (SESB) from January to May year 2009 / Adonis Jan Saliun - Jan Saliun, Adonis (Faculty of Business and Management, 2009)
This paper study on the sales analysis (electricity) by Sabah Electricity Sdn. Bhd. This study will focus on the company monthly sales from January to May 2009 for a period of five (5) months during the practical training. A rough ideas on the sales position of a company can be obtain by looking at it monthly sales. However, there is a need for reliable information in which every party can use for better decision making and to enhance the understanding over an organization’s actual business performance, and not just based on assumptions or an idea over a particular situation. For this reason, researcher will conduct a thorough sales analysis to analyze the sales with the organization’s goals, to identify problem that affect the sales and understand the problem that occurred in the sales of the company.